2018
DOI: 10.1186/s13012-018-0816-8
|View full text |Cite
|
Sign up to set email alerts
|

Audience segmentation to disseminate behavioral health evidence to legislators: an empirical clustering analysis

Abstract: BackgroundElected officials (e.g., legislators) are an important but understudied population in dissemination research. Audience segmentation is essential in developing dissemination strategies that are tailored for legislators with different characteristics, but sophisticated audience segmentation analyses have not been conducted with this population. An empirical clustering audience segmentation study was conducted to (1) identify behavioral health (i.e., mental health and substance abuse) audience segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 91 publications
7
59
1
Order By: Relevance
“…To our knowledge, no other studies have explicitly examined gender differences in public cancer stigma, although two studies in university student samples suggest that women are less likely than men to distance themselves from patients with cancer or refuse to help them [35, 36]. The finding that cancer stigma is higher in men is also consistent with a study about mental health stigma among US legislators that found that men were overrepresented among legislators with high levels of stigma (84% male versus 75% of all legislators included in the study) [37].…”
Section: Discussionsupporting
confidence: 65%
“…To our knowledge, no other studies have explicitly examined gender differences in public cancer stigma, although two studies in university student samples suggest that women are less likely than men to distance themselves from patients with cancer or refuse to help them [35, 36]. The finding that cancer stigma is higher in men is also consistent with a study about mental health stigma among US legislators that found that men were overrepresented among legislators with high levels of stigma (84% male versus 75% of all legislators included in the study) [37].…”
Section: Discussionsupporting
confidence: 65%
“…These findings suggest that the dissemination of evidence concerning C‐SBHPL, and potentially other evidence‐based behavioral health policies, should target mutable characteristics, as they might precede changes in policy support and, ultimately, policy adoption. Tailoring materials to be disseminated to ideologically conservative, moderate, and liberal legislators might also be beneficial …”
Section: Discussionmentioning
confidence: 99%
“…We calculated the nonresponse weights and applied them to adjust for these differences using a sample poststratification approach in which weighting classes were based on the full sample frame . The weights accounted for differences between the respondents and nonrespondents in gender, geographic region, and political party and have been used in previous analyses of the survey data set …”
Section: Methodsmentioning
confidence: 99%
“…As mentioned previously, dissemination strategies should be tailored to specific target stakeholders. The rationale for this is based in “audience segmentation,” which states that tailoring communication to groups who are similar to one another with regard to beliefs, identities, values, and roles will improve the effectiveness of dissemination (Purtle et al, 2018 ; Slater, 1996 ). Here, we briefly discuss different groups of individuals who play a role in disseminating school-based mental health services, how they are embedded in various contexts, their roles as change agents, and the specific behaviors they are in a position to engage in to support EBP implementation as part of routine school practice (see Table 1 ).…”
Section: Target Stakeholdersmentioning
confidence: 99%